Differences in drought tolerance in two almond cultivars: 'Lauranne' and 'Masbovera' - Herralde F. de; Savé R.; Biel C.; Batlle I.; Vargas F.J. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
The first experiment was carried out on adult trees, growing on seedling rootstocks; leaf water relations were studied determining pressure-volume curves. 'Masbovera' showed osmotic adjustment, reducing its Yp100 24 per cent whereas 'Lauranne' showed no significant variation. Cuticular transpiration rates were high in 'Lauranne' in June but it showed a 50 per cent reduction in September (differences were not significant between cultivars). Results on specific leaf weight showed no differences from April to June and September. On young potted trees, growing on GF-677 clonal rootstocks, daily drip fertirrigated, photosynthesis-light saturation curves were obtained. 'Masbovera' showed higher photosynthetic rates (106 per cent) and lower light compensation point (24 per cent) than 'Lauranne'. In a drought resistance trial, 'Masbovera' showed higher water use efficiency and higher regulation regarding hydraulic resistance than 'Lauranne'. From the results obtained 'Masbovera' should be considered better adapted than 'Lauranne' to be grown without irrigation under Mediterranean climatic conditions.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)